COMPREHENSIVE IMPLICATIONS OF "CURRICULAR FLEXIBILITY" IN EDUCATION - Marius Costel ESI (Association of Social and Educational Innovation, 2024)
The issue of curricular flexibility becomes relevant for the dimension of didactic sciences to the extent that it relates to the idea of curriculum design, to the multitude and diversity of teaching-learning methods or even to the idea of adaptability to the individual needs of pupils. Also, such a problem reveals ways of approaching education in relation to the idea of change at the level of the society. Given such assumptions, our approach first aims to identify what the main reasons and needs that underlie curricular flexibility are.          The purpose of this paper is to investigate and propose effective methods of implementing the concept of "curricular flexibility" having as epistemic coordinates the increase in the relevance and adaptability of the educational system to the individual needs and the particularities of pupils, as well as the ways of implementing the curricular flexibility in schools.          The curricular flexibilization is an educational approach which intends to respond to diversity and the changes in the dynamics of the modern society. This flexibility finds its foundation in the recognition that each pupil has different needs, interests and learning paces. By implementing the curricular flexibility, schools can respond more effectively to these individual differences, by providing a more personalized and relevant education.